2013
DOI: 10.1523/jneurosci.5855-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Is Required for Exercise-Induced Adult Hippocampal Neurogenesis

Abstract: Voluntary wheel running has long been known to induce precursor cell proliferation in adult hippocampal neurogenesis in rodents. However, mechanisms that couple activity with the promitotic effect are not yet fully understood. Using tryptophan hydroxylase (TPH) 2 deficient (Tph2-deficient) mice that lack brain serotonin, we explored the relationship between serotonin signaling and exercise-induced neurogenesis. Surprisingly, Tph2-deficient mice exhibit normal baseline hippocampal neurogenesis but impaired acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
143
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(157 citation statements)
references
References 35 publications
11
143
0
3
Order By: Relevance
“…The mechanism of compensation could have significant clinical relevance for restoring serotonin homeostasis in models of disease. For Tph2 -/-mice, although no change in overall proliferation was detected, there is a deficiency in the transition from type-1 stem cells to type-2 progenitors with an altered balance of precursor cell proliferation and cell death rate, accompanied by changes in the number of Sox2-expressing cells (Klempin et al, 2013). We suggested population changes on the cellular level in the absence of serotonin as potential compensatory mechanism that maintains the progenitor cell pool and thus homeostasis in Tph2 -/-mice.…”
Section: Animal Models: Addressing the Controversy Of Serotonin's Rolmentioning
confidence: 89%
See 2 more Smart Citations
“…The mechanism of compensation could have significant clinical relevance for restoring serotonin homeostasis in models of disease. For Tph2 -/-mice, although no change in overall proliferation was detected, there is a deficiency in the transition from type-1 stem cells to type-2 progenitors with an altered balance of precursor cell proliferation and cell death rate, accompanied by changes in the number of Sox2-expressing cells (Klempin et al, 2013). We suggested population changes on the cellular level in the absence of serotonin as potential compensatory mechanism that maintains the progenitor cell pool and thus homeostasis in Tph2 -/-mice.…”
Section: Animal Models: Addressing the Controversy Of Serotonin's Rolmentioning
confidence: 89%
“…It is important to define serotonin's essential roles in brain function and behavior, as it is equally important to 3 discover the regulators and interactive pathways by which serotonin mediates brain function. In this regard, we have recently tested serotonin action in a loss-of-function model in which the availability of brain-derived serotonin is selectively depleted (Alenina et al, 2009, Klempin et al, 2013. These data together with others from genetically modified mouse models shed a distinct light on the mechanisms proposed in earlier studies to be reviewed here.…”
Section: Serotonin Plays a Role In Many Homeostatic Systems As Evidenmentioning
confidence: 92%
See 1 more Smart Citation
“…Physical exercise has been recognized as one important approach to fight against mood disorders. The underlying mechanisms include adult hippocampal neurogenesis, alterations of brain blood perfusion, modulation of neuroinflammation, increased expression of neurotrophic factors in the brain, modulation of synaptic transmission and regulation of neurotransmitters such as serotonin [14][15][16][17][18][19][20][21][22]. Interestingly, a series of studies have shown the effects of physical exercise on gut microbiota dynamics, suggesting that gut microbiota regulation might act as one mediator for the effects of exercise on the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the exercise-induced brain benefits might as well be modulated through gut microbiota changes. For instance, serotonin is required for running induced benefits on neurogenesis [16,17], while gut the major source of serotonin production in the body [37]; GF mice exhibited altered serotonin signaling as well as relevant behaviors [9,14,38], suggesting that GF mice might lack the benefits of exercise on neurogenesis. Future studies are required to systemically examine such possibilities.…”
Section: Introductionmentioning
confidence: 99%